Institutional diversity in the euro area: Any evidence of convergence? - Pérez-Moreno, Salvador Jesús; Bárcena-Martín, Elena María (My University, 2017)
In recent years differences in the institutional structure across euro area countries are becoming a cause of concern both for some individual Member States and for the functioning of the Economic and Monetary Union (EMU). From a global competitiveness perspective, we deal with the diversity in the institutional environment in the EMU. In particular, we assess whether the changes in the state of institutions provide convergence across euro area countries between 2006 and 2015. In addition, among the institutional indicators considered, we compute which institutional aspect contributes more to overall inequality in the state of institutions, as well as the contribution of each country to inequality considering as benchmark the country with the highest institutional quality. According to these country contributions, we highlight distinct patterns of convergence between ‘core’ and ‘periphery’ euro area countries and raise potential links between the institutional changes across euro area countries and both the differences in the intensity of the financial and economic crisis, and the policy responses in terms of fiscal consolidation applied by the respective national governments.
Keywords: Europeísmo; Institutions; Convergence; Euro area